Os conceitos mais recorrentes de modelagem matemática (no ensino) encontrados em teses brasileiras defendidas de 2015 a 2022. - PIMENTEL, Jhonata Klark Souza (2025)
This research presents a survey of the most common concepts of mathematical modeling (in teaching) found in Brazilian theses defended from 2015 to 2022. A data analysis was carried out through access to the CAPES theses database, having detected the theses defended in the period in question. Through a draw, 8 (eight) works were chosen, each of them defended in a different year. These “concepts / definitions” were extracted, which were included in a table along with information about the theses. Then, conceptual reiterations were located, given the attempt to find aspects or characteristics that were common to two or more of them. After this analysis, it was possible to identify the most recurrent concepts of mathematical modeling found in the works, which followed the concepts of authors such as Burak (1992), Bassanezi (2006), Biembengut and Hein (2005), Barbosa (2001) and Almeida, Silva and Vertuan (2012). It is noteworthy that the use of mathematical modeling as a pedagogical strategy enriches the teaching-learning process and prepares students to face complex life problems.